78 IGCS gynecology oncology global curriculum and mentorship program in mozambique: challenges and results of an overseas surgical training program. (18th September 2019) - Changule, D; Rangeiro, R; Daud, S; Ribeiro, M; Luis, E; Mabota, F; Cintra, GF; Moretti-Marques, R; Vieira, MA; Salcedo, MP; Baker, ES; Lorenzoni, C; et al.
Abstract : Objectives: To describe the implementation of the IGCS Gynecologic Oncology Global Curriculum and Mentorship Program (Global Curriculum) in Mozambique. Methods: The Global Curriculum is a training program for regions that do not have formal training in Gynecologic Oncology. The Mozambique program is a collaboration between Maputo Central Hospital, five institutions in Brazil and MD Anderson Cancer Center. In January 2016, three Obstetrician-Gynecologists were selected as the Global Curriculum fellows. They follow an on-line curriculum, receive quarterly visits from international mentors, participate in monthly tumor boards using Project ECHO and enter case logs into the REDcap system. Results: To date, there have been 9 visits to Mozambique. Each visit consists of didactic lectures, surgical training, multi-disciplinary care and the management of preivansive desease. Between visits, monthly videoconferences are held to discuss patient cases. A total of 91 surgeries have been perfomed, including 45 radical hysterectomies, 11 cold knife conizations and 14 radical vulvectomies. Six colposcopy and LEEP courses were held with 202 attendees from all provinces of the country, 174 colposcopies and 35 LEEPs perfomed. In August 2018, a patient underwent radical hysterectomy and it was the first time this procedure was perfomed exclusively by Mozambican surgeons. Conclusions: The IGCS model of surgical training is feasible and has already shown good results for the oncology patients and fellows in Mozambique.